2013
DOI: 10.1007/s13679-013-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Low Back Pain: Is There a Weight of Evidence to Support a Positive Relationship?

Abstract: Obesity and low back pain (LBP) are responsible for significant morbidities and financial expenditure. Numerous studies have demonstrated a positive relationship between obesity and LBP, but a concurrent investigation of causality is often omitted. Spinal clinicians routinely prescribe exercise and weight loss for obese patients with LBP, despite a paucity of literature evaluating why obesity might cause LBP or how exercise and weight loss might be suitable treatments for LBP. Etiologies have tended to focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 98 publications
1
11
0
2
Order By: Relevance
“…Because disorders of lipid metabolism are considered essential for initiating the long, drawn-out process of atherosclerosis development, our results are in accordance with the hypothesis that atherosclerosis of the lumbar vessels is significant as a mechanism leading to LBP. Although lipid levels may indirectly affect LBP through obesity, which has been considered to result in increased mechanical load on the lumbar structure [ 30 ], our results showed a significant relationship between LBP and lipid levels after adjustment of BMI. These results may imply the existence of another pathway contributing to the development of LBP other than obesity.…”
Section: Discussionmentioning
confidence: 57%
“…Because disorders of lipid metabolism are considered essential for initiating the long, drawn-out process of atherosclerosis development, our results are in accordance with the hypothesis that atherosclerosis of the lumbar vessels is significant as a mechanism leading to LBP. Although lipid levels may indirectly affect LBP through obesity, which has been considered to result in increased mechanical load on the lumbar structure [ 30 ], our results showed a significant relationship between LBP and lipid levels after adjustment of BMI. These results may imply the existence of another pathway contributing to the development of LBP other than obesity.…”
Section: Discussionmentioning
confidence: 57%
“…In the field of prevention of LBP with weight reduction due to lifestyle modification, data is scarce and general conclusions cannot be deducted 33 . However, there are findings to support the claim that a reduction of the level of systemic inflammation by means of physical exercise, dieting and ultimately weight loss can help obese patients manage their LBP 37 . Specifically, the reduction of the levels of systemic inflammation leads to a decrease of the inflammatory insult on neurons and improves pain thresholds and pain regulation, thus enabling better responses to mechanical strain or stimuli 37 .…”
Section: Low Back Pain and οBesitymentioning
confidence: 97%
“…Obesity, more narrowly, has been shown to relate LBP and general musculoskeletal pain 33,35,36 . Most of the studies however try to establish a link between obesity and low back pain instead of investigating the physiological causality 37 . According to hypotheses made in studies, the surplus adipose tissue in obese patients applies further mechanical pressure or increased shear on load bearing joints, like the lumbar spine structures 38 .…”
Section: Low Back Pain and οBesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given these widely reported associations between lifestyle behavioural factors and low back pain, it is suggested that targeting these as part of low back pain management could improve patient outcomes [ 7 , 10 , 11 ]. While international guidelines for weight management recommend behavioural modification interventions as the preferred approach to managing weight loss and healthy lifestyle there is limited evidence to guide such care in patients with low back pain [ 9 ].…”
Section: Introductionmentioning
confidence: 99%